Negative electrode amorphous active material degree characterization method and application thereof in quality detection of negative electrode amorphous active material
By roasting the negative electrode amorphous active material in an inert atmosphere and using crystal references to calculate its amorphous energy storage in a lithium-ion battery, the problem of inability to effectively calculate amorphous energy storage in the prior art is solved, and an accurate measurement of the degree of improvement of amorphousness and electrical performance is achieved.
Patent Information
- Application Number
- CN202411694618.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is difficult to effectively calculate amorphous energy storage, and it is impossible to quantitatively analyze the impact of amorphous degree on the improvement of material reactivity, resulting in large errors.
By calculating the negative electrode amorphous active material under an inert atmosphere to the material temperature threshold for calculating, the amorphous structure was eliminated, and the cells were assembled separately using crystalline reference and unfired same material to record the energy changes during charging and discharging to calculate the amorphous energy storage.
This avoids the complex destination of amorphous energy storage, realizes accurate quantitative analysis of amorphous energy storage, and improves the accuracy of measuring amorphous degree and the degree of electrical performance improvement.
Smart Images

Figure CN119827539A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery materials, and in particular to a method for characterizing the degree of amorphous negative electrode active materials and an application thereof in quality detection of amorphous negative electrode active materials. Background Art
[0002] The amorphous state (also called non-crystalline state) is a special form of material existence, corresponding to the crystalline state. The molecules or atoms of crystalline materials are arranged in an orderly and uniform manner, while the molecules or atoms of amorphous materials lack long-range order, that is, there is no periodic arrangement structure like crystals, which causes them to have different physical and chemical properties from crystals. It is a microstructural parameter. Amorphous energy storage is based on energetics, which measures the degree of reduction of reaction barriers in the system of amorphous materials compared to crystalline materials, and is closer to practical applications. Both can reflect the reactivity of the material.
[0003] For negative electrode materials of lithium-ion batteries, a high degree of amorphism is accompanied by a lower difficulty in lithium insertion and an increased rate of lithium insertion. At present, the main materials for lithium battery amorphous negative electrodes are amorphous carbon and amorphous silicon. Amorphous carbon improves the directional restrictions of lithium insertion between graphite layers and increases the rate of lithium insertion. On the one hand, amorphous silicon improves the ability to insert lithium. On the other hand, the chaotic atomic arrangement and large atomic spacing make amorphous silicon have uniform and reversible volume changes compared to crystalline silicon, which solves the problem of anisotropic expansion of crystalline silicon and is the future development direction of negative electrode main materials.
[0004] The mainstream method for characterizing amorphous is the degree of amorphism, which has its own defects and needs to be characterized by energetics, as follows: 1. Characterization by XRD diffraction pattern Principle: Amorphization causes the XRD diffraction intensity of the material to become lower and the diffraction range to expand, that is, the peak height in the diffraction pattern becomes lower and the peak width becomes larger. The area change rate compared with standard crystalline silicon is the degree of amorphism.
[0005] formula: Where: is the degree of amorphism, A is the diffraction peak area of the material to be tested, and A0 is the diffraction peak area of standard crystalline silicon.
[0006] Defect: When the peak height becomes lower and the peak width becomes larger, the diffraction peak area does not necessarily become larger, causing the calculation result to be negative and the error to be too large.
[0007] 2. Characterization by coupling XRD diffraction pattern with internal standard method Principle: Based on method 1, a known amount of standard sample (such as crystalline silicon) is added to the material, the content of the standard sample is calculated based on the peak area, and the crystallinity is then obtained through the actual content, and then the degree of amorphization, i.e., the degree of amorphism, is obtained.
[0008] formula: ; Where: For amorphous degree, is the crystallization mass fraction of the sample to be tested, is the Rietveldscale factor of the crystallized material, ZM is the mass of the unit cell, V is the unit cell volume, n is the number of unit cells in the sample group, is the content of standard sample mixed in the sample, is the standard sample content calculated from the XRD pattern.
[0009] Disadvantages: Precise crystal phase composition is required, otherwise the quantitative result is the sum of amorphous and unknown crystals; the X-ray absorption coefficients of the added standard sample and the sample to be tested need to be close, otherwise absorption errors will occur and the number of parameters required for calculation is too large; it is difficult to determine the mixing of the standard sample, and the XRD diffraction pattern needs to be refined.
[0010] 3. Raman spectroscopy & nuclear magnetic resonance (NMR) & infrared spectroscopy (FTIR) The amorphous regions and crystallized regions of the material respond differently to optical and magnetic signals, and the degree of amorphism is determined based on the output information. The test has high accuracy, but its analytical capabilities are insufficient for samples with more complex structures.
[0011] 4. Differential Scanning Calorimetry (DSC) Principle: Amorphous materials have poor thermodynamic stability and are easily broken into amorphous state and transformed into a crystalline state during heating. Therefore, during heating, there is a difference in heat change between the crystalline region and the non-crystalline region. By measuring this difference, the crystallinity of the material can be calculated.
[0012] Disadvantages: Differential thermal analysis measures the amorphous degree of materials in the hot state, causing irreversible damage to the materials; however, this method is the first to focus on the combination of amorphous degree and system, that is, the measurement of amorphous degree requires comprehensive characterization based on the performance and function of amorphous materials in the system.
[0013] The amorphous degree obtained by the above method and the formula for calculation can be used to obtain the amorphous energy storage as follows: Where: For amorphous energy storage, For amorphous degree, is the melting enthalpy of the material, is the melting point of the material, is the melting point of the material.
[0014] For the characterization of material amorphism, the degree of amorphism is usually measured first, and then the amorphous energy storage is calculated based on the amorphous degree. However, most of the analysis of amorphism of various materials only stops at the degree of amorphism, and amorphous energy storage is rarely reported. This is because the measurement and calculation of amorphous degree is relatively simple. However, although the existing test methods quantify the degree of amorphism, they cannot quantitatively analyze the degree of improvement in the reactivity of the material. The error of further calculating the amorphous energy storage based on the amorphous degree that cannot be quantitatively analyzed is higher. Therefore, how to overcome the above-mentioned technical problems and defects has become a key issue that needs to be solved. Summary of the invention
[0015] In order to solve the problem that amorphous degree cannot be used to effectively calculate amorphous energy storage, the present invention provides a method for characterizing the degree of negative electrode amorphous active materials and its application in quality detection of negative electrode amorphous active materials.
[0016] The technical solution adopted by the present invention to solve the above technical problems is as follows: The first aspect of the present invention provides a method for characterizing the degree of amorphous active material of a negative electrode, comprising the following steps: S1. The negative electrode amorphous active material is heated to a material temperature threshold under an inert atmosphere and calcined, wherein the temperature threshold is greater than or equal to the temperature at which the negative electrode amorphous active material crystallizes to obtain a crystalline reference; S2. Assemble batteries using a crystal reference and an unbaked negative electrode active material of the same type, charge the two batteries at a constant current to the same voltage, and record the energy E obtained by the two batteries during the charging process. 充1 and E 充2 , where the amorphous energy storage E generated during the charging process a充 =E 充2 -E 充1 ; and / or, Discharge the two batteries at a constant current until they are empty, and record the energy E released by the two batteries during the discharge process. 放1 and E 放2 , where the amorphous energy storage E generated during the discharge process a放 =E 放2 -E 放1 .
[0017] Optionally, in step S1, the density of the negative electrode amorphous active material is 0.05-0.15 g / cm 3 .
[0018] Optionally, in step S1, the calcination process of the negative electrode amorphous active material is: heating the negative electrode amorphous active material to a material temperature threshold at a rate of 10-20°C / min under an inert atmosphere, and continuing to calcine at the temperature threshold for 120-240 min.
[0019] Optionally, in step S1, the negative electrode amorphous active material includes one or more of silicon-carbon material, silicon-oxygen material, hard carbon material and soft carbon material.
[0020] Optionally, the temperature threshold of the silicon-carbon material is 700~1200°C; the temperature threshold of the silicon-oxygen material is 800~1300°C; the temperature threshold of the hard carbon material is 1300~1500°C; and the temperature threshold of the soft carbon material is 1200~1400°C.
[0021] Optionally, in step S1, the inert atmosphere includes one or more of nitrogen, argon, and hydrogen.
[0022] Optionally, in step S1, after the crystalline reference is obtained by calcining, annealing is performed to cool the object, and the annealing process is as follows: the crystalline reference is slowly annealed at 50-100°C / h to room temperature.
[0023] Optionally, in step S2, the battery is a half-cell using a lithium sheet as a counter electrode.
[0024] The second aspect of the present invention provides an application of a method for characterizing the degree of negative electrode amorphous active material in the quality detection of negative electrode amorphous active material, so as to characterize the obtained E a充 and / or E a As a judgment condition, when E a充 and / or E a放 When it is greater than or equal to the set value, the negative electrode amorphous active material is judged to be qualified; when E a充 and / or E a放 When it is less than the set value, the negative electrode amorphous active material is judged to be unqualified.
[0025] Optionally, the set value is 0.34~0.59 kJ / mol.
[0026] According to the method for characterizing the degree of negative electrode amorphous active material provided by the present invention, the negative electrode amorphous active material is heated to the material temperature threshold under inert atmosphere conditions and then calcined to eliminate the amorphous structure; then the crystalline reference is slowly annealed to room temperature; annealing too quickly is avoided so that the negative electrode amorphous active material stores energy again; then E a充 and E a放 The error comparison of the energy value is carried out to verify the accuracy of the method for characterizing the degree of amorphous active materials in the negative electrode; the method for characterizing the degree of amorphous active materials adopted by the present invention avoids the problem that the destination of amorphous energy storage is complicated and cannot be quantitatively analyzed. The material properties of amorphous energy storage and amorphous degree are combined with the actual application process of the battery cell, which improves the guidance of this parameter. Furthermore, the degree of utilization of amorphism can be analyzed through the results, avoiding the increased cost of increasing the amorphous degree that cannot be utilized in the production process of negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the description of the embodiments of the present invention will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0028] Figure 1 It is a schematic diagram of the principle reaction of a method for characterizing the degree of negative electrode amorphous active material provided by one embodiment of the present invention; Figure 2 This is a SEM image of silicon-carbon material. DETAILED DESCRIPTION
[0029] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0030] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0031] In one embodiment, the first aspect of the present invention provides a method for characterizing the degree of amorphous active material of a negative electrode, comprising the following steps: S1. The negative electrode amorphous active material is heated to a material temperature threshold under an inert atmosphere and calcined, wherein the temperature threshold is greater than or equal to the temperature at which the negative electrode amorphous active material crystallizes to obtain a crystalline reference; S2. Use the crystal reference and the unbaked negative active material to assemble the battery, charge the two batteries to the same voltage at constant current, the voltage is 1.8~2v; record the energy E obtained by the two batteries during the charging process 充1 and E 充2 , where the amorphous energy storage E generated during the charging process a充 =E 充2 -E 充1 ; and / or, Discharge the two batteries at a constant current until they are empty, and record the energy E released by the two batteries during the discharge process. 放1 and E 放2 , where the amorphous energy storage E generated during the discharge process a放 =E放2 -E 放1 .
[0032] From the perspective of energetics, the destination of amorphous energy storage in a lithium battery reaction system can be described as: When charging, the material consumes amorphous energy storage, and at the same time, the amorphous energy storage of the new phase begins to increase, and the same is true for discharge. During the cycle, some amorphous energy storage does not completely react and continues to remain in the material, and the spontaneous transformation of the material from amorphous to a low-energy state crystalline state will also consume some energy. Therefore, the whereabouts of amorphous energy storage are complex and cannot be quantitatively analyzed. Furthermore, there is a utilization rate of amorphous energy storage during the lithium battery charging and discharging process, which is why the degree of amorphism cannot be quantitatively measured to measure the degree of improvement in electrical performance. Therefore, if the complexity of energy quantification can be solved, the degree of improvement in electrical performance caused by the amorphous structure can be quantitatively measured.
[0033] Correct amorphous energy storage can quantitatively analyze the barrier-reducing capability of amorphous materials in reaction systems. For lithium battery reaction systems, using correct amorphous energy storage to characterize the reaction activity of the negative electrode main material can more accurately measure the degree of improvement of electrical performance by amorphism.
[0034] The principle of the method for characterizing the degree of amorphous active material of the negative electrode of the present invention is: taking charging as an example, Figure 1 As shown in the figure, the black line is a schematic diagram of the energy of the charging state of a certain negative electrode main material. E0 is the initial energy. During the charging process, the material first obtains energy to reach the activated state, and E a is the activation energy, and then reaches the final state, E 充 The energy obtained by the material during the charging process. The gray line is a schematic diagram of the energy of the amorphous state of the same chemical formula. Amorphous energy storage increases the basic energy of the material, E 0’ is the initial energy. During the charging process, the initial energy of the material is high and it is easier to reach the activated state. a’ is the activation energy, and then reaches the final state, E 充’ It is the energy obtained by the material during the charging process. Obviously, E0-E 0’ =E 充 -E 充’ =E a’ -E a =Amorphous energy storage, so as long as any set of energy values is obtained, the amorphous energy storage value under the battery reaction system can be calculated, and the same is true for discharge.
[0035] In the method for characterizing the degree of negative electrode amorphous active material of the present invention, the negative electrode amorphous active material is first heated to the material temperature threshold under an inert atmosphere and calcined to eliminate the amorphous structure; Afterwards, the crystal reference and the unbaked negative active material of the same type were used to assemble batteries, and the two batteries were charged to full power at a constant voltage, and the energy E obtained by the two batteries during the charging process was recorded. 充1 and E 充2 , where the amorphous energy storage E generated during the charging process a充 =E 充2 -E 充1 ;or, Discharge the two batteries at a constant current until they are empty, and record the energy E released by the two batteries during the discharge process. 放1 and E 放2 , where the amorphous energy storage E generated during the discharge process a放 =E 放2 -E 放1 ; E a充 and E a放 The energy values were compared with each other to verify the accuracy of the method for characterizing the degree of amorphous active materials in the negative electrode.
[0036] The method for characterizing the degree of amorphous active materials used in the present invention avoids the problem that the destination of amorphous energy storage is complicated and cannot be quantitatively analyzed. The material properties of amorphous energy storage and amorphous degree are combined with the actual application process of the battery cell, which improves the guidance of this parameter. Furthermore, the degree of utilization of amorphism can be analyzed through the results, avoiding the increased cost of increasing the amorphous degree that cannot be utilized during the production of negative electrode materials.
[0037] The method for characterizing the degree of amorphous active materials used in the present invention can not only characterize the energy storage of the amorphous active materials by using energy difference, but also characterize the energy storage of the amorphous active materials by using parameters related to energy such as capacity.
[0038] In one embodiment, in step S1, the density of the negative electrode amorphous active material is 0.05-0.15 g / cm 3 .
[0039] Specifically, the density of the negative electrode amorphous active material is 0.05 g / cm 3 , 0.06g / cm 3 , 0.07g / cm 3 , 0.08g / cm 3 , 0.09g / cm 3 , 0.1g / cm 3 , 0.11g / cm 3 , 0.12g / cm 3 , 0.13g / cm 3 , 0.14g / cm 3 or 0.15g / cm 3In a preferred embodiment, the density of the negative electrode amorphous active material is 0.08-0.12 g / cm 3 .
[0040] The density of the negative electrode amorphous active material is 0.05~0.15g / cm 3 When the negative electrode amorphous active materials are distributed loosely and evenly, the negative electrode amorphous active materials are prevented from sticking together during the calcination process, which affects the calcination effect.
[0041] In one embodiment, in step S1, the calcination process of the negative electrode amorphous active material is: heating the negative electrode amorphous active material to a material temperature threshold at a rate of 10-20°C / min under an inert atmosphere, and continuing to calcine at the temperature threshold for 120-240 minutes.
[0042] Specifically, the heating rate of the negative electrode amorphous active material under an inert atmosphere is: any point value among 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min, 15°C / min, 16°C / min, 17°C / min, 18°C / min, 19°C / min or 20°C / min, or a range value composed of any two point values; in a preferred embodiment, the heating rate of the negative electrode amorphous active material under an inert atmosphere is 10~15°C / min.
[0043] When the heating rate of the negative electrode amorphous active material is 10-20°C / min under inert atmosphere conditions, sintering of the negative electrode amorphous active material during the calcination process is avoided to affect the calcination effect.
[0044] Specifically, the time for the negative electrode amorphous active material to continue to be calcined at the temperature threshold is: any point value among 120min, 130min, 140min, 150min, 160min, 170min, 180min, 190min, 200min, 210min, 220min, 230min or 240min, or a range value composed of any two point values; in a preferred embodiment, the time for the negative electrode amorphous active material to continue to be calcined at the temperature threshold is 160-200min.
[0045] When the negative electrode amorphous active material continues to be calcined for 120 to 240 minutes at the temperature threshold, the negative electrode amorphous active material can be fully burned to achieve the purpose of eliminating the amorphous structure.
[0046] In one embodiment, in step S1 , the negative electrode amorphous active material includes one or more of silicon-carbon material, silicon-oxygen material, hard carbon material and soft carbon material.
[0047] Specifically, silicon-carbon materials include one or more of nano silicon carbon, vapor deposited silicon carbon, hard carbon-coated outer layer silicon carbon, soft carbon-loaded silicon carbon, and multidimensional structured nano silicon carbon; silicon-oxygen materials include one or more of nano silicon-oxygen, carbon-coated silicon-oxygen, and multidimensional structured nano silicon-oxygen; hard carbon materials include one or more of biomass hard carbon and multidimensional nano hard carbon; soft carbon materials include one or more of amorphous graphite and multidimensional structured nano graphite.
[0048] In one embodiment, the temperature threshold of the silicon-carbon material is 700-1200°C; the temperature threshold of the silicon-oxygen material is 800-1300°C; the temperature threshold of the hard carbon material is 1300-1500°C; and the temperature threshold of the soft carbon material is 1200-1400°C.
[0049] Specifically, when the silicon-carbon material, silicon-oxygen material, hard carbon material and soft carbon material are nano-materials or multi-dimensional structures, the negative electrode amorphous active material is heated to the lower limit of the material temperature threshold; it is suitable for long-term roasting; when the silicon-carbon material, silicon-oxygen material, hard carbon material and soft carbon material are coated materials, the negative electrode amorphous active material is heated to the upper limit of the material temperature threshold; it is suitable for short-time roasting.
[0050] In one embodiment, in step S1 , the inert atmosphere includes one of nitrogen, argon, and hydrogen.
[0051] Specifically, the nitrogen in the present application is high-purity nitrogen; the argon is high-purity argon; and the hydrogen is high-purity hydrogen. Under an inert atmosphere, the negative electrode amorphous active material can be prevented from reacting with other substances to affect the purity of the negative electrode amorphous active material.
[0052] In one embodiment, in step S1, after the crystalline reference is obtained by calcining, annealing is performed to cool the object. The annealing process is as follows: the crystalline reference is slowly annealed at 50-100°C / h to room temperature.
[0053] Specifically, the annealing rate of the crystallization reference is: any point value among 50℃ / h, 55℃ / h, 60℃ / h, 65℃ / h, 70℃ / h, 75℃ / h, 80℃ / h, 85℃ / h, 90℃ / h, 95℃ / h or 100℃ / h, or a range value consisting of any two point values; in a preferred embodiment, the annealing rate of the crystallization reference is 50~75℃ / h.
[0054] When the annealing rate of the crystallization reference is 50~100℃ / h, avoid annealing too fast so that the crystallization reference stores energy again.
[0055] In one embodiment, in step S2, the battery is a half-cell using a lithium sheet as a counter electrode.
[0056] In one embodiment, the half-cell includes a negative electrode plate, a separator and a lithium plate; the negative electrode plate includes a negative electrode collector and a negative electrode active material layer arranged on at least one side of the surface of the negative electrode collector, and the negative electrode active material layer includes a negative electrode amorphous active material, a conductive agent and a binder.
[0057] Specifically, the conductive agent includes one or more of amorphous carbon, SuperP, Ketjen black, acetylene black, carbon nanotubes, carbon nanofibers and graphene; the binder includes one or more of lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, styrene-butadiene rubber, styrene-acrylic emulsion, lithium polyacrylate, sodium polyacrylate, potassium polyacrylate, lithium alginate, sodium alginate or potassium alginate.
[0058] In the half-cell provided by the present invention, the diaphragm can be any diaphragm material suitable for lithium-ion batteries in the art, for example, it can be a combination of one or more including but not limited to Celgar2500, single-layer PP (polypropylene), single-layer PE (polyethylene), polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fiber.
[0059] The half-cell provided by the present invention also includes an electrolyte.
[0060] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0061] In some of the embodiments, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0062] In some of the embodiments, the solvent may include one or more of ethylene carbonate, propylene carbonate, ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate, fluoroethylene carbonate (FEC), methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0063] In one embodiment, the second aspect of the present invention provides an application of a method for characterizing the degree of negative electrode amorphous active material in the quality detection of negative electrode amorphous active material to characterize the obtained E a充 and / or E a As a judgment condition, when E a充 and / or E a放 When it is greater than or equal to the set value, the negative electrode amorphous active material is judged to be qualified; when E a充 and / or E a放 When it is less than the set value, the negative electrode amorphous active material is judged to be unqualified.
[0064] Specifically, the present invention is carried out by a充 and / or E a放 When compared with the set value, when E a充 and / or E a放 When it is greater than or equal to the set value, the negative electrode amorphous active material is judged to be qualified; when E a充 and / or E a放 When it is less than the set value, the negative electrode amorphous active material is judged as unqualified, and the role of the amorphous active material in the battery operation can be calculated more accurately. Compared with other methods, the results obtained by this method are more in line with the actual application process of the battery cell, which improves the guidance of this parameter. Furthermore, the utilization degree of amorphous can be analyzed through the results, avoiding the increased cost of increasing the amorphous degree that cannot be utilized during the production process of negative electrode materials.
[0065] In one embodiment, the set value is 0.34-0.59 kJ / mol.
[0066] Specifically, the set values are: 0.34 kJ / mol, 0.35 kJ / mol, 0.36 kJ / mol, 0.37 kJ / mol, 0.38 kJ / mol, 0.39 kJ / mol, 0.4 kJ / mol, 0.41 kJ / mol, 0.42 kJ / mol, 0.43 kJ / mol, 0.44 kJ / mol, 0.45 kJ / mol, 0.46 kJ / mol, 0.47 kJ / mol, 0.4 8kJ / mol, 0.49kJ / mol, 0.5kJ / mol, 0.51kJ / mol, 0.52kJ / mol, 0.53kJ / mol, 0.54kJ / mol, 0.55kJ / mol, 0.56kJ / mol, 0.57kJ / mol, 0.58kJ / mol or 0.59kJ / mol, or a range consisting of any two values; in a preferred embodiment, the set value is 0.4~0.5 kJ / mol.
[0067] When the set value is 0.34~0.59 kJ / mol, the higher it is, the more amorphous energy storage the main material can utilize, and the smaller the difference with the theoretical value is, indicating that the utilization efficiency of the amorphous active material is higher.
[0068] The beneficial effects of the present invention are further illustrated below in conjunction with embodiments.
[0069] In order to make the invention purpose, technical scheme and beneficial technical effect of the present invention clearer, the present invention is further described in detail below in conjunction with examples. However, it should be understood that the examples of the present invention are only for explaining the present invention, not for limiting the present invention, and the examples of the present invention are not limited to the examples given in the specification. The specific experimental conditions or operating conditions not specified in the examples are made under conventional conditions, or are made under the conditions recommended by the material supplier.
[0070] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0071] In the following examples, the reagents, materials and instruments used, unless otherwise specified, can be purchased commercially or obtained by synthetic methods known in the art.
[0072] Table 1 Characterization of the degree of amorphous active material of the negative electrode of Examples 1-10 Example 1 This embodiment provides a method for characterizing the degree of amorphous active material of a negative electrode, comprising the following steps: 1. Preparation method of negative electrode amorphous active material: The silicon-carbon negative electrode material was heated to 1000°C at a rate of 10°C / min in a nitrogen atmosphere and calcined at this temperature for 150 min. The crystallized reference was slowly annealed at 50°C / h to room temperature; 2. Preparation of negative electrode sheet Preparation of negative electrode sheet 1: The crystal reference, conductive carbon black (SuperPLi), and binder (SA, 3wt%) were mixed in a ratio of 8:1:1, and deionized water was added as a solvent to prepare a slurry with a solid content of 70%, and stirred evenly. The slurry was evenly coated on both surfaces of the negative electrode current collector copper foil with a thickness of 10μm, dried in a vacuum drying oven at 80℃ for 12h, and then cut into electrode sheets with a diameter of 14mm using a cutting machine for standby use.
[0073] Preparation of negative electrode sheet 2: The uncalcined amorphous active material of the negative electrode, conductive carbon black (SuperPLi), and binder (SA, 3wt%) were mixed in a ratio of 8:1:1, and deionized water was added as a solvent to prepare a slurry with a solid content of 70%, and stirred evenly. The slurry was evenly coated on both surfaces of the negative electrode current collector copper foil with a thickness of 10μm, dried in a vacuum drying oven at 80℃ for 12h, and then cut into electrode sheets with a diameter of 14mm using a cutting machine for standby use.
[0074] 3. Preparation of positive electrode A lithium sheet with a diameter of 15.6 mm is used as the positive electrode; 4. Preparation of diaphragm: Celgar 2500 was used as the diaphragm.
[0075] 5. Preparation of electrolyte: LiPF6 solution is used as the electrolyte.
[0076] 6. Preparation of lithium-ion batteries: In an Ar-filled glove box (water content <0.01ppm, oxygen content <0.01ppm), the positive electrode sheet, separator, and negative electrode sheet 1 prepared above are stacked in order, so that the separator is located between the positive electrode sheet and the negative electrode sheet to play a role of isolation. The electrode assembly is placed in a steel shell, and the prepared electrolyte is injected. After vacuum packaging, standing, formation, shaping and other processes, a lithium-ion battery 1 is obtained.
[0077] In an Ar-filled glove box (water content <0.01ppm, oxygen content <0.01ppm), the positive electrode sheet, separator, and negative electrode sheet 2 prepared above are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role. The electrode assembly is placed in a steel shell, and the prepared electrolyte is injected. After vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery 2 is obtained.
[0078] 7. Characterization method of the degree of amorphous active material in negative electrode After assembling lithium-ion battery 1 and lithium-ion battery 2, place them at room temperature of 25°C for 12 hours and then charge them to full capacity at a constant voltage. The energy E obtained by the two batteries during the charging process is recorded respectively.充1 and E 充2 , where the amorphous energy storage E generated during the charging process a充 =E 充2 -E 充1 =1.93kJ / mol; Discharge lithium-ion battery 1 and lithium-ion battery 2 to empty state at constant current, and record the energy E released by the two batteries during the discharge process. 放1 and E 放2 , where the amorphous energy storage E generated during the discharge process a放 =E 放2 -E 放1 =1.91 kJ / mol; E a充 and E a放 The converted amorphous degree is 3.9%.
[0079] Embodiments 2 to 9 Examples 2 to 9 are used to illustrate a method for characterizing the degree of amorphous active material of a negative electrode disclosed in the present invention, and include most of the operating steps in Example 1, except that: The heating rates and annealing rates used in Examples 2 to 9 are shown in Table 1.
[0080] Comparative Example 1 Comparative Example 1 is used to compare and illustrate a method for characterizing the degree of amorphous active material of a negative electrode disclosed in the present invention, and includes most of the operating steps in Example 1, except that: The preparation of the negative electrode sheet 1 is not included; Characterization method of the degree of amorphous active material of negative electrode: The XRD diffraction spectrum characterization method was used to calculate the amorphous degree of the lithium ion battery 2, and the result showed that the amorphous degree of the material was 48.25%.
[0081] Comparative Example 2 Comparative Example 2 is used to compare and illustrate a method for characterizing the degree of amorphous active material of a negative electrode disclosed in the present invention, and includes most of the operating steps in Example 1, except that: The preparation of the negative electrode sheet 1 is not included; Characterization method of the degree of amorphous active material of negative electrode: The lithium-ion battery 2 was characterized by Raman spectroscopy, and the amorphous degree of the material was calculated to be 30.91%.
[0082] Then the amorphous energy storage formula was used for calculation, and the amorphous energy storage results were 23.96 kJ / mol and 15.35 kJ / mol, which were quite different.
[0083] From the test results in Table 1 and the calculation results of Comparative Examples 1-2, it can be seen that the amorphous energy storage value of the reaction calculated by this method is in the range of 2 kJ / mol, which is equivalent to an amorphous structure with an amorphous degree of 4.07% playing a role in the battery operation. Compared with the calculation methods of Comparative Examples 1 and 2, the results obtained by this method are more in line with the actual application process of the battery cell.
[0084] During the calcination process, when the temperature is increased at 10~20℃ / min, E a放 With E a充 The values of are close, and the calculation results of amorphous degree have high accuracy; During the annealing process, when the temperature is slowly annealed at 50-100℃ / h to room temperature, E a放 With E a充 The values of are relatively close, and the calculation results of amorphous degree have high accuracy.
[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for characterizing the degree of amorphous active material of a negative electrode, characterized in that: The following steps are involved: S1. The negative electrode amorphous active material is heated to a temperature threshold under an inert atmosphere and calcined, wherein the temperature threshold is greater than or equal to the temperature at which the negative electrode amorphous active material crystallizes to obtain a crystalline reference; S2. Assemble batteries using a crystalline reference and an unbaked amorphous negative active material of the same type, charge the two batteries at constant current to the same voltage, and record the energy E obtained by the two batteries during the charging process. 充1 and E 充2 , where the amorphous energy storage E generated during the charging process a充 =E 充2 -E 充1 ; and / or, Discharge the two batteries at a constant current until they are empty, and record the energy E released by the two batteries during the discharge process. 放1 and E 放2 , where the amorphous energy storage E generated during the discharge process a放 =E 放2 -E 放1 .
2. The method for characterizing the degree of negative electrode amorphous active material according to claim 1, characterized in that: In step S1, the density of the negative electrode amorphous active material is 0.05-0.15 g / cm 3 .
3. The method for characterizing the degree of negative electrode amorphous active material according to claim 1, characterized in that: In step S1, the calcination process of the negative electrode amorphous active material is: heating the negative electrode amorphous active material to a material temperature threshold at a rate of 10-20°C / min under an inert atmosphere, and continuing to calcine at the temperature threshold for 120-240 minutes.
4. The method for characterizing the degree of negative electrode amorphous active material according to claim 1, characterized in that: In step S1 , the negative electrode amorphous active material includes one or more of silicon-carbon material, silicon-oxygen material, hard carbon material and soft carbon material.
5. The method for characterizing the degree of negative electrode amorphous active material according to claim 4, characterized in that: The temperature threshold of the silicon-carbon material is 700-1200°C; the temperature threshold of the silicon-oxygen material is 800-1300°C; the temperature threshold of the hard carbon material is 1300-1500°C; and the temperature threshold of the soft carbon material is 1200-1400°C.
6. The method for characterizing the degree of negative electrode amorphous active material according to claim 1, characterized in that: In step S1, the inert atmosphere includes one or more of nitrogen, argon, and hydrogen.
7. The method for characterizing the degree of negative electrode amorphous active material according to claim 1, characterized in that: In step S1, after the crystalline reference is obtained by calcining, annealing is performed to cool the object. The annealing process is as follows: the crystalline reference is slowly annealed at 50-100°C / h to room temperature.
8. The method for characterizing the degree of negative electrode amorphous active material according to claim 1, characterized in that: In step S2, the battery is a half-cell using a lithium sheet as a counter electrode.
9. Application of the method for characterizing the degree of negative electrode amorphous active material according to any one of claims 1 to 8 in quality detection of negative electrode amorphous active material, characterized in that: The E a充 and / or E a As a judgment condition, when E a充 and / or E a放 When it is greater than or equal to the set value, the negative electrode amorphous active material is judged to be qualified; when E a充 and / or E a放 When it is less than the set value, the negative electrode amorphous active material is judged to be unqualified.
10. Application of the method for characterizing the degree of negative electrode amorphous active material according to claim 9 in quality detection of negative electrode amorphous active material, characterized in that: The set value is 0.34~0.59 kJ / mol.